1999
DOI: 10.1039/a809164a
|View full text |Cite
|
Sign up to set email alerts
|

Structure, morphology and surface properties of nanostructured ZrO2 particles

Abstract: Nanocrystalline zirconium dioxide particles have been produced by means of thermal decomposition of a liquid metal organic precursor in a flow reactor system. X-Ray diffraction patterns show that the powder consists of a mixture of the monoclinic and tetragonal phase and that the phase fractions depend on the experimental conditions during the preparation as well as on the subsequent thermal treatment of the sample. The mean particle diameter of the synthesized powders is ca. 40-50 A ˚as estimated from the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…The preceding bands in each part are assigned to low-coordinated Zr 4 (or Ce 4 )-OH, whereas the subsequent bands are assigned to low-coordinated O-H derived from H 2 O. 12 Lowcoordinated Zr 4 (or Ce 4 )-OH on Ce-ZrO 2 is dominant even after desorption of CO 2 at 300°C. It has been reported that the formation of the stronger Lewis acid (Zr 4 or Ce 4 ) and base (surface O 2À ) sites is favorable for CO 2 activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preceding bands in each part are assigned to low-coordinated Zr 4 (or Ce 4 )-OH, whereas the subsequent bands are assigned to low-coordinated O-H derived from H 2 O. 12 Lowcoordinated Zr 4 (or Ce 4 )-OH on Ce-ZrO 2 is dominant even after desorption of CO 2 at 300°C. It has been reported that the formation of the stronger Lewis acid (Zr 4 or Ce 4 ) and base (surface O 2À ) sites is favorable for CO 2 activation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the formation of the stronger Lewis acid (Zr 4 or Ce 4 ) and base (surface O 2À ) sites is favorable for CO 2 activation. 12,13 The more pronounced intensity attributed to the formation of planar polydentate carbonates (1466 and 1406 cm À1 ) on Ce-ZrO 2 indicates the closeness of cations, which is characteristic of the tetragonal structure of ZrO 2 . 14 For zirconia the bands assigned to bidentate carbonates (1550 and 1331 cm À1 ) and hydrogen carbonates (1630, 1427, and 1219 cm À1 ) disappear after evacuation at 300°C, whereas the bands due to hydrogen carbonates (1653, 1431, and 1200 cm À1 ) appear on supported Fe 3 O 4 catalyst after evacuation at 300°C.…”
Section: Resultsmentioning
confidence: 99%
“…Let us compare the in#uence of thermal treatment on phase fractions of nanocrystalline zirconia prepared by di!erent routes. A recent study carried out by Benfer et al (33) focused on zirconia prepared by (i) CVD from organic precursors and (ii) #ame hydrolysis from ZrCl (Degussa). Our zirconia were prepared by pyrolysis of nitrates at 6003C (I-6.9) and 9003C (II-13.2).…”
Section: Discussionmentioning
confidence: 99%
“…Monocrystalline titania anatase (93 m 2 /g) was prepared by chemical vapour deposition method [27] and wet impregnated with Pd(NO 3 ) 2 AE 2H 2 O (Merck) to obtain a metal loading of 2. TiO 2 particles were produced by means of thermal decomposition of titanium isopropoxide vapour in a flow reactor.…”
Section: Methodsmentioning
confidence: 99%